2017
DOI: 10.1371/journal.pone.0182381
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 encapsulated in PLGA microparticles accelerates wound healing of skin ulcers

Abstract: Lipoxin A4 (LXA4) is involved in the resolution of inflammation and wound healing; however, it is extremely unstable. Thus, to preserve its biological activities and confer stability, we encapsulated LXA4 in poly-lactic-co-glycolic acid (PLGA) microparticles (LXA4-MS) and assessed its application in treating dorsal rat skin lesions. Ulcers were sealed with fibrin adhesive and treated with either LXA4-MS, unloaded microparticles (Un-MS), soluble LXA4, or PBS/glue (vehicle). All groups were compared at 0, 2, 7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
1
26
1
2
Order By: Relevance
“…In addition, the results showed that a fewer amount of TNFα was secreted in cells treated with LXA4. These results are consistent with previous studies, where treatment with LXA4 resulted in a decrease in pro-inflammatory cytokines (Gaudin et al, 2018;Pouliot et al, 2000;Reis et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the results showed that a fewer amount of TNFα was secreted in cells treated with LXA4. These results are consistent with previous studies, where treatment with LXA4 resulted in a decrease in pro-inflammatory cytokines (Gaudin et al, 2018;Pouliot et al, 2000;Reis et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…While the role of 12‐ and 15‐HETE in tissue repair is largely unclear, LXA 4 has been implicated in tissue regeneration as it could reduce inflammation and promote re‐epithelialization in the eye . Moreover, the administration of LXA 4 ‐containing microparticles in a rat model of skin wound healing promoted wound closure, angiogenesis and collagen deposition, potentially by inducing IL‐4, TGFβ1 and tissue repair macrophages . Intriguingly, 12‐/15‐LOX is generally highly expressed during type 2 immune responses, for example after exposure to house dust mite or during intestinal nematode infection .…”
Section: Roles Of Eicosanoids In Tissue Repairmentioning
confidence: 99%
“…8 Moreover, the administration of LXA 4 -containing microparticles in a rat model of skin wound healing promoted wound closure, angiogenesis and collagen deposition, potentially by inducing IL-4, TGFb1 and tissue repair macrophages. 59 Intriguingly, 12-/15-LOX is generally highly expressed during type 2 immune responses, for example after exposure to house dust mite or during intestinal nematode infection. 15,60 This may suggest that 12/ 15-LOX also plays important roles in epithelial barrier repair in mucosal tissues such as the airways and intestine.…”
Section: Lipoxins and Resolvins-anti-inflammatory Mediators Of Barriementioning
confidence: 99%
“…The microspheres were prepared using a polymer, the co-glycolic poly-lactic acid (PLGA) as a scaffold. PLGA is widely used for preparation of microspheres because it is a biodegradable and biocompatible polymer (Fredenberg et al, 2011;Pereira et al, 2015;Reis et al, 2017;Lorencetti-Silva et al, 2019). This material allows the release of encapsulated molecules in a controlled manner for long periods and from a single administration, which keeps the concentrations of the encapsulated substance constant (Ford Versypt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aim of this study was to investigate the role of leukotriene B4 in the differentiation of cells from the monocytic lineage (J774A.1) into osteoclasts, after stimulation with leukotriene B4 encapsulated in microspheres. This therapeutic strategy, based on the use of polylactic-co-glycolic acid microspheres (PLGA), promote a sustained delivery of lipid mediator over time since lipid mediators are extremely labile (Nicolete et al, 2009;Santos et al, 2011;Pereira et al, 2015;Reis et al, 2017;Lorencetti-Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%